2004
DOI: 10.1186/1471-2393-4-15
|View full text |Cite
|
Sign up to set email alerts
|

'Perinatal outcome in preterm premature rupture of membranes with Amniotic fluid index < 5 (AFI < 5)

Abstract: Background: Our purpose was to determine whether AFI<5 cm after preterm premature rupture of the membranes (PPROM) is associated with an increased risk of perinatal morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
6
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 9 publications
7
30
6
1
Order By: Relevance
“…Our data indicated that oligohydramnios was associated with an earlier gestational age at PPROM. This finding is in disagreement with data published by most of the authors [1,[8][9][10]12] and we believe that this association is the result of gestational age itself rather than a smaller single deepest vertical pocket.…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…Our data indicated that oligohydramnios was associated with an earlier gestational age at PPROM. This finding is in disagreement with data published by most of the authors [1,[8][9][10]12] and we believe that this association is the result of gestational age itself rather than a smaller single deepest vertical pocket.…”
Section: Discussioncontrasting
confidence: 57%
“…This finding is consistent with studies of Borna et al [9], Kurdoglu et al [8] and Kacerovsky et al [10] and in contrast to results published by Mercer et al [6], Vermillion et al [3] and Piazze et al [12]. Interestingly, a study by Abbasalidadeh et al [11] showed a longer latent phase with SDP <2cm when compared to cases with a normal SDP.…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations